New strategies of development in the information age. - YAMAGUCHI, Kaoru (1995)
Proposes an economy consisting of three features, i.e. information-sharing networks, self-management and participatory democracy, and sustainable development. Concludes that developing countries can attain an information-age development without passing through the capital-intensive and pollution-ridden industrialization of the industrial age.